Relasi Islam dan Psikologi: Ikhtiar Menuju Integrasi Keilmuan - Nuzulul Khair (Institut Ilmu Keislaman Annuqayah, 2019)
The research examines the relationship between Islam and Psychology as an attempt to reach scientific integration. By far, psychological studies have been developed with western perspectives that emphasize empirical experiments as the primary source to result in scientific products. However, the psychological concepts produced with western perspectives are not sufficient to absorb religious values. The research offers alternative discourses that were attempted to improve methodological seriousness and maturity, namely by providing implicit discourse in the scientific development process of Islamic psychology. The article showed that Islam is a universal religion that abounds with religious values that have profound sources written in Quran and Sunnah. Also, Islam is brim with the wisdom of the religious leaders that can be a foundation to burgeon Islamic psychological concepts. Islam has its methodological basis that can be used as a reference to enhance psychological theories, ranging from textual, philosophical, to Sufistic approaches.